The Interview: Citra Politik Kim Jong Un Dalam Hegemoni Film Amerika - Nasution, Faiz Albar; Indainanto, Yofiendi Indah; Muhammad Ardian; Saraan, Muhammad Imanuddin Kandias (Talenta Publisher, 2023)
This study examines film The Interview to determine hegemonic process of political power relations in American films. North Korea is known as a closed country that strongly opposes western domination, especially America. Foreign media always describe North Korean government as a dictator, meaning absolute power of leader. In contrast, film The Interview depicts a humorous figure of North Korean leader by showing figure of Kim Jong Un who enjoys American culture. The plot of Twits in this film depicts uprising that took place to make North Korea a democracy. Qualitative descriptive research method is used in analyzing film through approach of Gramsci hegemony theory about how hegemony process in the film The Interview. Data collection techniques through literature examination include books, journals, documents, and films. Data reduction, data visualization, and drawing conclusions are data analysis activities. The results of study show that dominant group tries to exert influence with concepts of mastery in a persuasive manner by presenting reality from a different point of view. The dominant people here are Americans who are trying to change mindset audience by seeing North Korea as an oppressed people. Leaders who have been known to be assertive, such as Kim Jong Un, who is feared by people, are portrayed as humorous figures with a love for American culture, which is a clear fact in their development that they often experience political tensions.